PENGARUH LABA BERSIH DAN ARUS KAS TERHADAP HARGA SAHAM STUDI EMPIRIS PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Yandra, Iin Syofia (LP2M Universitas Bina Bangsa, 2025)
This research is entitled The Effect of Net Profit and Cash Flow on Stock Prices Empirical Study on Banking Sector Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period. The purpose of this study is to find out how the effect of net income and cash flow partially, simultaneously and how big the influence variable is on stock prices in banks listed on the Indonesian stock exchange for the 2018-2022 period. This study uses descriptive statistical methods and multiple linear regression analysis using the SPSS Version 25 analysis tool. The results of this study indicate that net income has an effect on stock prices in the banking sector listed on the Indonesian stock exchange for the 2018-2022 period. And cash flow has a negative effect on stock prices in banking sector companies listed on the Indonesian stock exchange for the 2018-2022 period.